Answer:
rate this 5 stars or your gay
Step-by-step explanation:
Just do it
Answer:
144
Step-by-step explanation:
Answer:
The first store
Step-by-step explanation:
3sweaters->$44.99
4sweaters->x
x=4×44.99/3 x=$59.98
3sweaters->$52.00
4sweaters->x
x=4×52/3 x=$69.33
first store<second store
59.98<69.33
Answer:
.208
Step-by-step explanation:
Step-by-step explanation:
(2a+3b)(4a²-6ab+9b²
(2a+3b){(2a)²-2a×3b+(3b)²}
Because (a³+b³)=(a+b)(a²-ab+b²)
Therefore,
(2a+3b){(2a)²-2a×3b+(3b)²}
=(2a)³+(3b)³
By substituting the values , we get
- (2a)³+(3b)³
- (2×3)³+(3×(-5))³
- 6³+(-15)³
- 216+(-3375)
- 216-3375
- -3159